Existence of Fixed Points of a Pair of Self Maps under Weak Generalized Geraghty Contractions in Complete Partially Ordered Partial B-Metric Spaces (Global Journal of Science Frontier Research, 2016)
Abstract not found
Keywords: fixed points; weak contraction; altering distance function; geraghty type contraction coupled 3B1; 2212; admissible; partial b - metric; complete partial